Adjuvant Therapy With Mushroom Polysaccharides for Diabetic Complications - Jiang, Xue; Meng, Weiqi; Li, Lanzhou; Meng, Zhaoli; Wang, Di (Frontiers in Pharmacology, 2020)
Background Diabetic complications seriously endanger the health of most diabetic patients around the world. Most chemical hypoglycemic agents have adverse effects and are unable to improve the progression of diabetic complications. In recent years, a number of medicinal herbs have become increasingly popular for the treatment of diabetic complications due to their relative safety. Polysaccharides extracted from medicinal herbs with multiple pharmacological activities and low toxicity have been reported to be useful in the treatment of diabetic complications. Methods Primary studies with keywords including polysaccharide and diabetic complications were retrieved from the Web of Science and NCBI databases and were read and analyzed. Results Mushroom polysaccharides were proven to have positive effects on diabetic complications. Conclusions We studied the effects of mushroom polysaccharides on hyperglycemia and as adjuvant therapies for diabetic complications and summarized the applications and limitations of mushroom polysaccharides to better understand their application for the treatment of diabetic complications.